Long‐term outcomes of domiciliary intravenous iloprost in idiopathic and connective tissue disease‐associated pulmonary arterial hypertension. Issue 2 (20th September 2016) - Ramjug, Sheila; Hussain, Nehal; Hurdman, Judith; Elliot, Charlie A.; Sabroe, Ian; Armstrong, Iain J.; Billings, Catherine; Hamilton, Neil; Kiely, David G.; Condliffe, Robin
ABSTRACT: Background and objective: There are few published data on the efficacy of i.v. iloprost in pulmonary arterial hypertension (PAH). We present long‐term outcomes in PAH patients receiving i.v. iloprost in a large UK referral centre. Methods: Eighty patients with idiopathic PAH (iPAH, n = 46) or PAH associated with connective tissue disease (CTD‐PAH, n = 34) were identified as receiving domiciliary i.v. iloprost between January 1999 and April 2015. Baseline characteristics, doses achieved, functional class at follow‐up and survival data were retrieved from hospital databases. Results: Median maximum dose achieved was 4.6 ng/kg/min in the iPAH group and 5.0 ng/kg/min in CTD‐PAH patients. Exercise capacity significantly improved in the first 6 months of therapy in IPAH patients. Overall 1‐, 3‐ and 5‐year survival was 78%, 64% and 52% in iPAH ( P = 0.002) and 64%, 26% and 21% in CTD‐PAH. Independent predictors of survival were age and exercise capacity. Conclusion: We report improved survival to that previously reported in iPAH patients treated with domiciliary i.v. iloprost. This may be in part related to higher administered doses. Patients with CTD‐PAH had poorer survival, reinforcing the need for early transplantation referral in suitable patients. Abstract : From a large single centre, we report on our experience of the efficacy of long‐term i.v. iloprost in subjects with idiopathic pulmonary arterial hypertension (iPAH) and connective tissue disease‐associated PAH (CTD‐PAH). Despite few published studies, reported outcomes have been poor. However, we have found improved survival to that previously reported in iPAH patients treated with domiciliary i.v. iloprost.